THE NEW APPROACH FOR STUDY THE GROWTH REGULATION OF VARIOUS FORMS OF CHILDREN HEMANGIOMA - Z. Vadachkoria; L. Dzidziguri; G. Ghibradze; I. Modebadze; M. Mikadze; D. Dzidziguri (Ukrainian Medical Stomatological Academy, 2016)
The aim of our study was the identification of the thermostable protein complexes in the cells of infant's hemangiomas. In order to identify the TPC from children capillary hemangioma components the TPC from adult rat pancreas as a control were used. In compare to control sample the TPC from the children capillary hemangioma is different in the quantitative content, as its low molecular weight (12-17 KD), as well as a relatively high-molecular component. The effect of the TPC from Children capillary hemangioma on the proliferative activity of the brain cells of the infant rats also were studied. It has been determined that the intraperitoneal injection of mentioned TPC decreases the mitotic activity of heterotypic cells (rat brain).